P-type silicon as hole supplier for nitride-based UVC LEDs. (28th February 2019) - Cho, Sang June; Liu, Dong; Seo, Jung-Hun; Dalmau, Rafael; Kim, Kwangeun; Park, Jeongpil; Gong, Jiarui; Zhao, Deyin; Wang, Fei; Yin, Xin; Jung, Yei Hwan; Lee, In-Kyu; et al.
Abstract: The ineffective p-type doping of nitrides using magnesium (Mg), the best available dopant, has limited the development and performance of all III-nitride-based devices, including bipolar junction transistors and light emitting diodes (LEDs). For nitride-based ultraviolet (UV) LEDs, as the Al composition increases for achieving shorter wavelengths (e.g. <280 nm) into the UVC spectral range, the p-type doping issue, which causes very inefficient hole injection, becomes more severe than ever. In this work, we report the detailed study of using p-type Si as a hole supplier for high-Al composition UVC LEDs. We first describe the method of Si/GaN junction formation, where the lattice-mismatch challenge between Si and GaN is overcome by using a 0.5 nm thick Al2 O3 layer at the interface. This serves as a physical separation layer between the two materials as well as a passivation, tunneling, and thermal buffer layer. High-resolution transmission electron microscope image illustrates the high-quality interface between Si and GaN. We further detail the hole transport mechanism of the p–p Si/GaN isotype junction through both simulations and experiments. The enhanced hole concentration in the AlGaN/AlN multiple quantum wells (MQWs) due to the use of p-type Si as the hole supplier is verified through comparison with conventional UVC LEDs. Finally, high-performance UVC LEDs made with AlN/AlGaN (Al: 72%) MQWs employing p-type Si as their hole suppliers are demonstrated experimentally to serve as an example of the novel hole injector strategy.